Genetic and Transcription Profile Analysis of Tissue-Specific Anthocyanin Pigmentation in Carrot Root Phloem - Bannoud, Florencia (2021)
In purple carrots, anthocyanin pigmentation can be expressed in the entire root, or it can display tissue specific-patterns. Within the phloem, purple pigmentation can be found in the outer phloem (OP) (also called the cortex) and inner phloem (IP), or it can be confined exclusively to the OP. In this work, the genetic control underlying tissue-specific anthocyanin pigmentation in the carrot root OP and IP tissues was investigated by means of linkage mapping and transcriptome (RNA-seq) and phylogenetic analyses; followed by gene expression (RT-qPCR) evaluations in two genetic backgrounds, an F2 population (3242) and the inbred B7262. Genetic mapping of ‘root outer phloem anthocyanin pigmentation’ (ROPAP) and inner phloem pigmentation (RIPAP) revealed colocalization of ROPAP with the P1 and P3 genomic regions previously known to condition pigmentation in different genetic stocks, whereas RIPAP co-localized with P3 only. Transcriptome analysis of purple OP (POP) vs. non-purple IP (NPIP) tissues, along with linkage and phylogenetic data, allowed an initial identification of 28 candidate genes, 19 of which were further evaluated by RT-qPCR in independent root samples of 3242 and B7262, revealing 15 genes consistently upregulated in the POP in both genetic backgrounds, and two genes upregulated in the POP in specific backgrounds. These include seven transcription factors, seven anthocyanin structural genes, and two genes involved in cellular transport. Altogether, our results point at DcMYB7, DcMYB113, and a MADS-box (DCAR_010757) as the main candidate genes conditioning ROPAP in 3242, whereas DcMYB7 and MADS-box condition RIPAP in this background. In 7262, DcMYB113 conditions ROPAP.